Karakteristik Kondisi Mangrove di Desa Taddan Kabupaten Sampang - Firman Farid Muhsoni (Universitas Trunojoyo Madura, 2020)
Mangroves are intertidal plants found along tropical and non-tropical coastlines which is flooded by tides in brackish areas. Mangroves ecosystems have experienced a very large decrease in area especially in Madura region. This research was conducted in Taddan Village, Camplong District, Sampang. The objectives of this research were to identify mangrove vegetation, mangrove area and mangrove characteristics. The area of mangroves in the research location was 48 ha. There were 7 types of mangroves found, e.g Rhizophora apiculata, Rhizophora stylosa, Rhizophora mucronata, Sonneratia alba, Sonneratia caseolaris, Avicennia marina and Avicennia alba. The type of substrate in the mangrove research location was mainly mud. The distribution pattern of mangroves at the research location tends to spread in groups, with a low level of mangrove diversity. The uniformity index value is balanced, or in other words, there are individuals who dominate. The average sediment depth is 24.7 cm, the average salinity is 36.7 ppt, the average water pH is 5.3, the average DO is 5.9 mg / l, the average water temperature is 31, 70C, the average soil pH is 6.4. Further analysis concluded that environmental parameters in the area was unsuitable for marine tourism.